ANALYSIS OF FINANCIAL STRATEGIES AND COGNITIVE SHIFTS IN “RICH DAD POOR DAD” BY ROBERT KIYOSAKI - Esanova Sevinch Sayidjon qizi,; Shavkatov Sherzod Shavkatovich, (TADQIQOTLAR, 2026)
Abstract:  This research is about wealth management, which is talked about in Robert Kiyosakis book, Rich Dad Poor Dad. The study looks at the difference between what people learn in school and what they need to know about money, which is called Financial IQ. It explains how assets and liabilities work in today’s economy. The study also looks at the things that stop people from getting wealthy and shows how to become financially independent by buying assets.